2021
DOI: 10.1021/acs.macromol.1c00605
|View full text |Cite
|
Sign up to set email alerts
|

Handedness Inversion in Chiral Nematic (Ethyl)cellulose Solutions: Effects of Substituents and Temperature

Abstract: Various acylates and phenylcarbamates of (ethyl)­cellulose (EC) were synthesized by acylation and carbanilation, respectively, of the residual hydroxyls of an EC (ethyl DS = 2.50). The acyl substituents adopted were propionyl, butyryl, cyclohexanoyl, and adamantoyl groups, and the phenylcarbamoyl substituents included 3-chlorophenylcarbamoyl, 4-chlorophenylcarbamoyl, 3-methylphenylcarbamoyl, and bare phenylcarbamoyl groups. Chiral nematic mesophases of the EC derivatives, formed in chloroform, acetic acid (AA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…In contrast to CNCs, left-and right-handed cholesteric helices have been observed for cellulose derivative-based ChLCs. Most recently, Nishio et al [30,31] proposed that the effects of the substituents and temperature on the helical handedness of cellulosic ChLCs can be systematically interpreted in terms of the balance between the dispersion interaction and steric repulsion, based on their experimental data and the theoretical work of Osipov [30,31].…”
Section: Cellulosic Liquid-crystalsmentioning
confidence: 99%
“…In contrast to CNCs, left-and right-handed cholesteric helices have been observed for cellulose derivative-based ChLCs. Most recently, Nishio et al [30,31] proposed that the effects of the substituents and temperature on the helical handedness of cellulosic ChLCs can be systematically interpreted in terms of the balance between the dispersion interaction and steric repulsion, based on their experimental data and the theoretical work of Osipov [30,31].…”
Section: Cellulosic Liquid-crystalsmentioning
confidence: 99%
“…68 Cholesteric liquid crystalline mesophases can display left-or right-handed helices, and the chirality may switch depending on the solvent or the DS, which influences what polarizations of light are reflected by the mesophase. 55 Twisting power is defined as the inverse of the pitch; it is negative for left-handed and positive for right-handed structures. 55 While EC mesophases tend to be left-handed, substituting acetyl, acyl, and phenylcarbamoyl groups for the hydroxyls above a critical DS can alter the chirality, leading to right-handed helices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…55 Twisting power is defined as the inverse of the pitch; it is negative for left-handed and positive for right-handed structures. 55 While EC mesophases tend to be left-handed, substituting acetyl, acyl, and phenylcarbamoyl groups for the hydroxyls above a critical DS can alter the chirality, leading to right-handed helices. 37,53,55 In these modified EC polymers, the left-handed chiral nematic mesophases are reported to have a pitch more strongly dependent on concentration than the right-handed ones.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the side‐chain structure of the cellulose derivatives on their liquid crystallinity has also been well inspected. These studies revealed that the reflection color of cellulosic ChLC is highly sensitive to diverse side‐chain parameters including side‐chain length, bulkiness, and degree of substitution 32–35 . Based on these characteristics, ChLC formed by cellulose derivatives with PBA‐side groups can be expected to achieve enzyme‐free color sensing of glucose.…”
Section: Introductionmentioning
confidence: 99%